Vitamin D supplementation on prediabetic adults with vitamin D deficiency: a double-blind placebo-controlled randomized clinical trial: Vitamin D supplementation on prediabetic adults with vitamin D deficiency (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Hypovitaminosis D (